Relationship between vitamin D and depression: literature review (Research, Society and Development, 2022)
Depression is a mental disorder with a chronic and recurrent course, being one of the most common and fastest growing illnesses in the world. Vitamin D is a steroid hormone that acts mainly in the regulation of bone metabolism, however, in view of the presence of vitamin D receptors throughout the body, several studies have been and are being carried out in order to prove its role in other functions. The objective of this work is to demonstrate the relationship between blood concentration of vitamin D and depression through an integrative literature review. The research consisted of searching for scientific articles in the PubMed and Scielo electronic databases, using the following descriptors in English and Portuguese: “vitamin D”, “blood concentration” and depression. In all, 1588 articles were found in the databases, but only 07 were used in this research. The selected articles show a significant relationship between vitamin D levels and the clinical picture of depression, in which individuals with vitamin D deficiency had a higher risk of developing and maintaining a depressive state, as well as their supplementation seems to reduce this state. However, further studies are needed to elucidate the relationship between vitamin D and depression, in addition to generating new information that demonstrates the importance of monitoring this nutrient and its use in the treatment of this pathology.